Sulphoraphane Improves Neuronal Mitochondrial Function in Brain Tissue in Acute Carbon Monoxide Poisoning Rats. Issue 6 (30th March 2017) - Bi, Mingjun; Li, Qin; Guo, Dadong; Ding, Xiaoyu; Bi, Weikang; Zhang, Yueheng; Zou, Yong
Abstract: Carbon monoxide (CO) poisoning is one of the leading causes of toxicity‐related mortality and morbidity worldwide, primarily manifested by acute and delayed central nervous system (CNS) injuries and other organ damages. However, its definite pathogenesis is poorly understood. The aim of this study was to explore the pathogenesis of the ultrastructural and functional impairment of mitochondria and the protection of sulphoraphane (SFP) at different dosages on hippocampus neurons in rats after exposure to CO. We found that CO poisoning could induce advanced cognitive dysfunction, while the mitochondrial ultrastructure of neurons in rats of the CO poisoning group was seriously damaged and mitochondrial membrane potential (ΔΨm) was accordingly reduced by transmission electron microscopy (TEM) and JC‐1 fluorescent probe assay. CO poisoning could also increase the expressions of both nuclear factor erythroid 2‐related factor 2 (Nrf‐2) and thioredoxin‐1 (Trx‐1) proteins and their mRNA in brain tissue with immunohistochemistry and quantitative PCR (qPCR) techniques. Early administration of either middle‐dose or high‐dose SFP could efficiently improve mitochondrial structure and function and enhance the antioxidative stress ability, thus exerting a positive effect against brain damage induced by acute CO poisoning.